Platinum-based nanowire electro-catalytic material as well as self-assembly preparation method and application thereof
By preparing platinum-based nanowires in self-assembly methods in reducing gas, the problem of difficult large-scale industrialization of platinum-based nanowire catalysts in the prior art is solved, and the surface cleaning and universality are achieved Catalyst preparation demonstrates excellent electrocatalytic performance and cost-reducing effect.
Patent Information
- Application Number
- CN202411306173.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-19
AI Technical Summary
It is difficult to realize the large-scale industrial production of platinum-based nanowire catalysts in the prior art, and the organic surfactants introduced in the liquid phase preparation method are not conducive to catalytic activity, making it difficult to achieve surface cleaning and high universality of platinum-based nanowire preparation.
Platinum-based nanowires are prepared by self-assembly method in reducing gas, and the adsorption energy difference of different crystals facing the gas is used to grow metal nanowires, avoiding the use of organic capsulating agents, and achieving controllable morphology The synthesis of platinum or platinum alloy nanowires are suitable for the synthesis of nanowires of different transition metals.
The preparation of platinum-based nanowire catalyst with clean surface and high universality is realized, which reduces the catalyst cost, demonstrates excellent electrocatalytic oxygen reduction performance, and is suitable for mass industrial production.
Smart Images

Figure CN119187583A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oxygen reduction catalytic materials and relates to a platinum-based nanowire electrocatalytic material and a self-assembly preparation method thereof and an application in oxygen reduction reactions. Background Art
[0002] Metal nanowires have excellent properties such as high conductivity, unique optical properties, and high aspect ratio. Compared with nanoparticles, one-dimensional platinum-based nanowire materials have a larger aspect ratio, which is conducive to building a self-supporting 3D network structure, providing a continuous electron transfer path, reducing the charge transfer resistance, improving the conductivity and kinetics of the electrode, and showing excellent performance in electrocatalysis.
[0003] In order to realize the preparation of nanowires, patent CN111313045 discloses a platinum-copper alloy nanowire and its preparation method and application. Although the platinum-copper alloy nanowire has strong catalytic activity and good stability as a methanol fuel cell anode catalyst, the catalyst is prepared by hydrothermal method, which is difficult to achieve large-scale industrialization. And the patent does not mention the method of preparing other transition metals and platinum to synthesize platinum-based nanowire catalysts, which is not universal. Patent CN105081341A provides a liquid phase synthesis method to obtain a platinum nanowire network. Although the preparation method is simple to operate and has a fast reaction speed, the method requires the use of an organic surfactant during synthesis, which is not conducive to catalytic activity and requires further treatment to remove the activator. At present, one-dimensional platinum-based nanowires are mainly prepared in liquid phase, and an activator is introduced in the preparation process, and it is difficult to achieve large-scale industrialization.
[0004] Therefore, there is an urgent need to develop a large-scale platinum-based nanowire catalyst with clean surface and high universality for use as a cathode catalyst in fuel cells. Summary of the invention
[0005] The purpose of the present invention is to provide a platinum-based nanowire electrocatalytic material and a self-assembly preparation method thereof and its application in oxygen reduction reaction. The preparation process of the present invention is simple, and the growth of multi-element metal nanowires can be controlled without complex organic capping reagents. Under the auxiliary action of reducing gas, different crystal faces have different adsorption energies for gas, and self-assembled metal nanowires are grown, which can be used for oxygen reduction reaction and have excellent catalytic performance.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] The first aspect of the present invention provides a method for preparing a platinum-based nanowire electrocatalytic material by self-assembly, comprising:
[0008] The platinum precursor salt and the transition metal precursor salt are mixed, heated in a reducing gas for reduction, and then heated in a diluted reducing gas for self-assembly to obtain a platinum-based nanowire electrocatalytic material;
[0009] Wherein, in the heating reduction, the reduction temperature is 100-200°C; in the heating self-assembly, the heating temperature is 250-300°C.
[0010] Furthermore, the reducing gas is hydrogen.
[0011] Furthermore, the diluted reducing gas is a mixture of hydrogen and inert gas.
[0012] Furthermore, the content of hydrogen is 5-10 vol%.
[0013] Furthermore, in the transition metal precursor salt, the transition metal is selected from at least one of iron, nickel, copper or cobalt.
[0014] Furthermore, in the platinum precursor salt and the transition metal precursor salt, the molar ratio of platinum to transition metal is (1-3):1.
[0015] Furthermore, the platinum precursor salt is chloroplatinite, and the transition metal precursor salt is selected from acetylacetonate.
[0016] Furthermore, the mixing process of the platinum precursor salt and the transition metal precursor salt also includes mixing them with a carrier.
[0017] Furthermore, the carrier is selected from porous carbon powder or titanium dioxide nanoparticles, and the amount used is 80-120 mg / 0.1 mmol Pt.
[0018] A second aspect of the present invention provides a platinum-based nanowire electrocatalytic material prepared by the method described above.
[0019] A third aspect of the present invention provides an application of a platinum-based nanowire electrocatalytic material, comprising using the platinum-based nanowire electrocatalytic material as an electrode material for preparing a fuel cell.
[0020] The present invention utilizes the self-assembly characteristics of metals in a hydrogen environment, and achieves the purpose of synthesizing pure platinum / binary platinum-based alloy nanowire metal materials with controllable morphology through a simple reduction reaction; at the same time, it avoids the influence of organic capping agents on the catalytic performance of metal nanomaterials, and achieves the purpose of preparing nanowire metal materials with clean surfaces. This method is universal and can be used for the synthesis of nanowires of different platinum-based metals. The prepared platinum-based alloy nanowire materials exhibit excellent electrocatalytic oxygen reduction performance due to low noble metal content and exposed high-index crystal faces. And compared with traditional liquid phase synthesis, this method will be more suitable for mass industrial production.
[0021] Compared with the prior art, the present invention has the following characteristics:
[0022] 1) The self-assembled metal nanowires prepared by the present invention have a low proportion of precious metal platinum, and the synergistic effect of transition metals makes the catalyst have high electrocatalytic oxygen reduction activity and greatly reduces the catalyst cost;
[0023] 2) The present invention adopts gas phase reaction, which is different from the traditional wet chemical method, has a simple preparation process and is suitable for large-scale batch production;
[0024] 3) The preparation process of the present invention does not require the introduction of any capping agent, the surface of the catalyst product is clean, no special treatment is required, the metal exposure area is large, excellent catalytic activity is exhibited, and it is green and environmentally friendly, reducing production costs;
[0025] 4) The present invention has high universality and is not only applicable to the preparation of self-assembled nanowires of pure platinum metal, but also to the self-assembly synthesis of alloy nanowires with different transition metal components and proportions. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A process flow chart of a self-assembly preparation method of a platinum-based nanowire electrocatalytic material in the present invention;
[0027] Figure 2 Transmission electron microscope photos of platinum-based nanowire electrocatalytic materials prepared in the present invention: (1) one-dimensional platinum-nickel alloy nanowires (Pt3Ni NWs) prepared in Example 1; (2) one-dimensional platinum-copper alloy nanowires (PtCu NWs) prepared in Example 2; (3) one-dimensional platinum-cobalt alloy nanowires (PtCo NWs) prepared in Example 3; (4) one-dimensional platinum-iron alloy nanowires (PtFe NWs) prepared in Example 6;
[0028] Figure 3 Transmission electron microscope photos of the one-dimensional platinum-cobalt alloy nanowires prepared by the present invention: (1) Pt:Co=1:1, Example 3, (2) Pt:Co=2:1, Example 4, (3) Pt:Co=3:1, Example 5; Particle size distribution diagram of the one-dimensional platinum-cobalt alloy nanowires prepared by the present invention: (4) Pt:Co=1:1, Example 3; (5) Pt:Co=2:1, Example 4; (6) Pt:Co=3:1, Example 5;
[0029] Figure 4 XRD and EDS element distribution of the one-dimensional platinum-cobalt alloy nanowires prepared in Example 3-5;
[0030] Figure 5 Transmission electron microscopy photos of porous carbon-supported one-dimensional platinum-based nanowires prepared in the present invention: (1) PtCo nanowires, Example 7; (2) PtFe nanowires, Example 8;
[0031] Figure 6The oxygen reduction performance of the one-dimensional platinum-cobalt alloy nanowires prepared in Example 3-5;
[0032] Figure 7 The oxygen reduction stability of the one-dimensional platinum-nickel alloy nanowires (Pt3Ni NWs) prepared in Example 1;
[0033] Figure 8 The oxygen reduction performance of the one-dimensional platinum-cobalt alloy nanowires prepared in Example 3 and the catalysts prepared at only 200°C and only 300°C;
[0034] Fig. 9 The oxygen reduction performance of the one-dimensional platinum-cobalt alloy nanowires prepared in Example 3 and nanowire catalysts prepared by other processes. DETAILED DESCRIPTION
[0035] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0036] A self-assembly preparation method of platinum-based nanowire electrocatalytic materials, such as Figure 1 As shown, the following steps are included:
[0037] S1: uniformly mixing a platinum metal precursor salt and a transition metal precursor salt to obtain a precursor powder, or uniformly mixing a platinum metal precursor salt, a transition metal precursor salt and a carrier to obtain a precursor powder;
[0038] S2: placing the precursor powder in a flowing reducing atmosphere and heating to reduce the platinum noble metal;
[0039] S3: The replacement reaction atmosphere is a mixed flow atmosphere of reducing gas / inert gas, and the transition metal and the noble metal are reduced together by heating and self-assembly to form a nanowire metal material.
[0040] In some specific embodiments, in step S1, the transition metal in the transition metal precursor salt is selected from at least one of iron, nickel, copper or cobalt.
[0041] In some specific embodiments, in step S1, the molar ratio of platinum to transition metal in the platinum precursor salt and the transition metal precursor salt is (1-3):1.
[0042] In some specific embodiments, the platinum precursor salt is chloroplatinite, such as potassium chloroplatinite.
[0043] In some specific embodiments, the transition metal precursor salt is selected from acetylacetonate, such as iron acetylacetonate, nickel acetylacetonate, copper acetylacetonate or cobalt acetylacetonate.
[0044] In some specific embodiments, in step S1, without adding a carrier, a self-supporting self-assembled metal nanowire can be formed, which has high conductivity, large metal exposed active area, and greatly improves the oxygen reduction electrochemical performance of the catalyst. Adding a carrier can form a supported self-assembled metal nanowire.
[0045] In some specific embodiments, the carrier is selected from porous carbon powder or titanium dioxide nanoparticles.
[0046] In some specific embodiments, the amount of the carrier is 80-120 mg / 0.1 mmol Pt.
[0047] In some specific embodiments, in step S1, the mixing of the platinum metal precursor salt and the transition metal precursor salt, or the mixing of the platinum metal precursor salt, the transition metal precursor salt and the carrier is achieved by grinding.
[0048] In some preferred embodiments, in order to prevent phase separation during the reduction process, it is necessary to grind repeatedly in a natural agate mortar until the solid powder has a uniform color.
[0049] In some specific embodiments, in step S2, the reducing gas used in the reducing atmosphere is hydrogen.
[0050] In some specific embodiments, in step S2, during the heating reduction, the reduction temperature is 100-200° C., and the reduction time is 10-180 min.
[0051] In step S2, part of the platinum precursor is pre-reduced to form nano-clustered platinum particles, which serve as platinum seeds to provide directional connection sites for the subsequent nucleation growth of transition metals.
[0052] In some specific embodiments, in step S2, the precursor powder is placed in a quartz boat and then placed in a quartz tube for heating to achieve thermal reduction.
[0053] In some preferred embodiments, the precursor powder should be able to be heated evenly and fully contact with the reaction gas, so it needs to be spread as flatly as possible on the quartz boat.
[0054] In some preferred embodiments, in step S2, before the heating reaction, the air in the reactor needs to be evacuated by an inert gas. More preferably, the inert gas is preferably argon, which needs to be introduced for 20 to 30 minutes to evacuate the air inside the cavity to prevent the metal precursor from being oxidized in the subsequent heating stage.
[0055] In some specific embodiments, in step S3, in the mixed flowing atmosphere, the reducing gas used is hydrogen, and the inert gas used is preferably argon.
[0056] In some more specific embodiments, the content of the reducing gas in the mixed flowing atmosphere is 5-10 vol%.
[0057] In some specific embodiments, in step S3, during the self-assembly process, the heating temperature is 250-300° C., and the reduction time is 0.5-6 h.
[0058] In step S3, the transition metal and the remaining platinum precursor are reduced together, and the nucleation continues preferentially on the pre-reduced platinum nanoclusters, and directionally grows into platinum-based alloy nanowires. Based on the different precursor salts added, pure platinum nanowires, platinum-cobalt nanowires, platinum-nickel nanowires, platinum-iron nanowires, and platinum-copper nanowires can be prepared.
[0059] In some specific embodiments, in step S3, the reduction product is dispersed in ethanol and ultrasonically washed to obtain a nanowire metal material.
[0060] The entire self-assembly preparation process of the present invention does not involve any organic capping agent, does not introduce organic substances, and avoids the influence of organic substances on catalytic performance; and does not require a complicated washing process. The reduction product is dispersed in deionized water (18.2 megohms) and anhydrous ethanol, and centrifuged twice by a centrifuge to remove the residual precursor salt; the storage is simple, and the product can be redispersed in anhydrous ethanol for long-term storage.
[0061] An application of a platinum-based nanowire electrocatalytic material comprises using the platinum-based nanowire electrocatalytic material as an electrode material for preparing a fuel cell.
[0062] This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0063] Oxygen reduction reaction test: The prepared catalyst was mixed into a uniform ink: 5 mg catalyst, 4 mL deionized water, 1 mL isopropanol, and 25 μL Nafion solution. The ink containing about 4 μg Pt was dropped into a 0.196 cm 2 The test was conducted on a rotating disk electrode and dried naturally. The three-electrode test method was used to conduct a 0.05-1.0V voltammetric cycle scan test in Ar-saturated 0.1M HClO4 and a 0-1.1V polarization curve test in O2-saturated 0.1M HClO4.
[0064] Accelerated stability testing: 30,000 cycles of accelerated cycling were performed in the voltage range of 0.6-1.0V, followed by oxygen reduction performance testing.
[0065] Fuel cell test: The prepared ink was sprayed on the proton exchange membrane as a cathode catalyst (0.1 mg Pt cm-2 ), 40 wt% commercial Pt / C catalyst was used as anode catalyst (0.05 mg Pt cm -2 ) was sprayed on the other side of the proton exchange membrane. A 235μm gas diffusion layer (28BC, SGL Carbon) was used for MEA assembly, and the fuel cell test system was the Scribner850e Fuel Cell Test System. Test conditions: 80℃, 0.5L min -1 H2, 0.5L min -1 O2, 2L min -1 Air.
[0066] Embodiment 1:
[0067] A self-assembled one-dimensional platinum-nickel alloy nanowire (Pt3Ni NWs), the preparation method of which comprises the following steps:
[0068] 1) Weigh 41.51 mg (0.1 mmol) of potassium chloroplatinite (K2PtCl4) and 8.56 mg (0.033 mmol) of nickel acetylacetonate (Ni(acac)2), grind them thoroughly in an agate mortar, and mix them evenly to obtain a precursor powder;
[0069] 2) The precursor powder is spread flat on a quartz boat, then placed in a quartz tube and placed in a tube furnace;
[0070] 3) Pass argon gas into the quartz tube for 20 minutes to exhaust the air in the quartz tube to prevent the metal from being oxidized during the heating process;
[0071] 4) Switch the gas to pure hydrogen at a flow rate of 200 ml / min; at the same time, raise the temperature of the tube furnace from room temperature to 200°C at a heating rate of 5°C / min and keep it at this temperature for 10 min;
[0072] 5) Switch the gas to a hydrogen / argon (v / v=5 / 95) mixed gas at a flow rate of 200 ml / min. At the same time, increase the temperature of the tube furnace from 200°C to 300°C at a heating rate of 5°C / min, keep the temperature for 0.5h, and then cool it down to room temperature naturally;
[0073] 6) After the reaction is completed, the gas is switched to argon, the residual hydrogen in the quartz tube is evacuated, and the reduced solid powder product is taken out;
[0074] 7) Washing: Add ethanol and deionized water for ultrasonic dispersion, then centrifuge, repeat twice. Disperse the washed sample into a small amount of anhydrous ethanol for storage to obtain self-assembled one-dimensional platinum-nickel alloy nanowires (Pt3Ni NWs).
[0075] Embodiment 2:
[0076] A self-assembled one-dimensional platinum-copper alloy nanowire (PtCu NWs), the preparation method of which comprises the following steps:
[0077] 1) Weigh 41.51 mg (0.1 mmol) of potassium chloroplatinite (K2PtCl4) and 26.17 mg (0.1 mmol) of copper acetylacetonate (Cu(acac)2), grind them thoroughly in an agate mortar, and mix them evenly to obtain a precursor powder;
[0078] 2) The precursor powder is spread flat on a quartz boat, then placed in a quartz tube and placed in a tube furnace;
[0079] 3) Pass argon gas into the quartz tube for 20 minutes to exhaust the air in the quartz tube to prevent the metal from being oxidized during the heating process;
[0080] 4) Switch the gas to pure hydrogen at a flow rate of 200 ml / min; at the same time, raise the temperature of the tube furnace from room temperature to 150°C at a heating rate of 5°C / min and keep it at that temperature for 30 min;
[0081] 5) Switch the gas to a hydrogen / argon (v / v=5 / 95) mixed gas at a flow rate of 200 ml / min. At the same time, increase the temperature of the tube furnace from 150°C to 250°C at a heating rate of 5°C / min, keep it for 1 hour, and then cool it down naturally to room temperature;
[0082] 6) After the reaction is completed, the gas is switched to argon, the residual hydrogen in the quartz tube is evacuated, and the reduced solid powder product is taken out;
[0083] 7) Washing: Add ethanol and deionized water for ultrasonic dispersion, then centrifuge, repeat twice. Disperse the washed sample into a small amount of anhydrous ethanol for storage to obtain self-assembled one-dimensional platinum-nickel alloy nanowires (Pt3Ni NWs).
[0084] Embodiment 3:
[0085] A self-assembled one-dimensional platinum-cobalt alloy nanowire (PtCo NWs), the preparation method of which comprises the following steps:
[0086] 1) Weigh 41.51 mg (0.1 mmol) of potassium chloroplatinite (K2PtCl4) and 25.72 mg (0.1 mmol) of cobalt acetylacetonate (Co(acac)2), grind them thoroughly in an agate mortar, and mix them evenly to obtain a precursor powder;
[0087] 2) The precursor powder is spread flat on a quartz boat, then placed in a quartz tube and placed in a tube furnace;
[0088] 3) Pass argon gas into the quartz tube for 20 minutes to exhaust the air in the quartz tube to prevent the metal from being oxidized during the heating process;
[0089] 4) Switch the gas to pure hydrogen at a flow rate of 200 ml / min; at the same time, raise the temperature of the tube furnace from room temperature to 200°C at a heating rate of 5°C / min and keep it at this temperature for 120 min;
[0090] 5) Switch the gas to a hydrogen / argon (v / v=5 / 95) mixed gas at a flow rate of 200 ml / min. At the same time, increase the temperature of the tube furnace from 200°C to 300°C at a heating rate of 5°C / min, keep it at that temperature for 2h, and then cool it down naturally to room temperature;
[0091] 6) After the reaction is completed, the gas is switched to argon, the residual hydrogen in the quartz tube is evacuated, and the reduced solid powder product is taken out;
[0092] 7) Washing: Add ethanol and deionized water for ultrasonic dispersion, then centrifuge, repeat twice. Disperse the washed sample into a small amount of anhydrous ethanol for storage to obtain self-assembled one-dimensional platinum-nickel alloy nanowires (Pt3Ni NWs).
[0093] Embodiment 4:
[0094] A self-assembled one-dimensional platinum-cobalt alloy nanowire (Pt2Co NWs), the preparation method of which comprises the following steps:
[0095] 1) Weigh 41.51 mg (0.1 mmol) of potassium chloroplatinite (K2PtCl4) and 12.86 mg (0.05 mmol) of cobalt acetylacetonate (Co(acac)2), grind them thoroughly in an agate mortar, and mix them evenly to obtain a precursor powder;
[0096] 2) The precursor powder is spread flat on a quartz boat, then placed in a quartz tube and placed in a tube furnace;
[0097] 3) Pass argon gas into the quartz tube for 20 minutes to exhaust the air in the quartz tube to prevent the metal from being oxidized during the heating process;
[0098] 4) Switch the gas to pure hydrogen at a flow rate of 200 ml / min; at the same time, raise the temperature of the tube furnace from room temperature to 200°C at a heating rate of 5°C / min and keep it at this temperature for 120 min;
[0099] 5) Switch the gas to a hydrogen / argon (v / v=5 / 95) mixed gas at a flow rate of 200 ml / min. At the same time, increase the temperature of the tube furnace from 200°C to 300°C at a heating rate of 5°C / min, keep the temperature for 3 hours, and then cool it down to room temperature naturally;
[0100] 6) After the reaction is completed, the gas is switched to argon, the residual hydrogen in the quartz tube is evacuated, and the reduced solid powder product is taken out;
[0101] 7) Washing: Add ethanol and deionized water for ultrasonic dispersion, then centrifuge, repeat twice. Disperse the washed sample into a small amount of anhydrous ethanol for storage to obtain self-assembled one-dimensional platinum-nickel alloy nanowires (Pt3Ni NWs).
[0102] Embodiment 5:
[0103] A self-assembled one-dimensional platinum-cobalt alloy nanowire (Pt3Co NWs), the preparation method of which comprises the following steps:
[0104] 1) Weigh 41.51 mg (0.1 mmol) of potassium chloroplatinite (K2PtCl4) and 8.57 mg (0.033 mmol) of cobalt acetylacetonate (Co(acac)2), grind them thoroughly in an agate mortar, and mix them evenly to obtain a precursor powder;
[0105] 2) The precursor powder is spread flat on a quartz boat, then placed in a quartz tube and placed in a tube furnace;
[0106] 3) Pass argon gas into the quartz tube for 20 minutes to exhaust the air in the quartz tube to prevent the metal from being oxidized during the heating process;
[0107] 4) Switch the gas to pure hydrogen at a flow rate of 200 ml / min; at the same time, raise the temperature of the tube furnace from room temperature to 200°C at a heating rate of 5°C / min and keep it at this temperature for 120 min;
[0108] 5) Switch the gas to a hydrogen / argon (v / v=5 / 95) mixed gas at a flow rate of 200 ml / min. At the same time, increase the temperature of the tube furnace from 200°C to 300°C at a heating rate of 5°C / min, keep the temperature for 3 hours, and then cool it down to room temperature naturally;
[0109] 6) After the reaction is completed, the gas is switched to argon, the residual hydrogen in the quartz tube is evacuated, and the reduced solid powder product is taken out;
[0110] 7) Washing: Add ethanol and deionized water for ultrasonic dispersion, then centrifuge, repeat twice. Disperse the washed sample into a small amount of anhydrous ethanol for storage to obtain self-assembled one-dimensional platinum-cobalt alloy nanowires (Pt3Co NWs).
[0111] Embodiment 6:
[0112] A self-assembled one-dimensional platinum-iron alloy nanowire (PtFe NWs), the preparation method of which comprises the following steps:
[0113] 1) Weigh 41.51 mg (0.1 mmol) of potassium chloroplatinite (K2PtCl4) and 35.32 mg (0.1 mmol) of iron acetylacetonate (Fe(acac)3) precursor, place the two in an agate mortar, grind them thoroughly, mix them evenly, and obtain a precursor powder;
[0114] 2) The precursor powder is spread flat on a quartz boat, then placed in a quartz tube and placed in a tube furnace;
[0115] 3) Pass argon gas into the quartz tube for 20 minutes to exhaust the air in the quartz tube to prevent the metal from being oxidized during the heating process;
[0116] 4) Switch the gas to pure hydrogen at a flow rate of 200 ml / min; at the same time, raise the temperature of the tube furnace from room temperature to 200°C at a heating rate of 5°C / min and keep it at this temperature for 60 min;
[0117] 5) Switch the gas to a hydrogen / argon (v / v=5 / 95) mixed gas at a flow rate of 200 ml / min. At the same time, increase the temperature of the tube furnace from 200°C to 300°C at a heating rate of 5°C / min, keep it at that temperature for 2h, and then cool it down naturally to room temperature;
[0118] 6) After the reaction is completed, the gas is switched to argon, the residual hydrogen in the quartz tube is evacuated, and the reduced solid powder product is taken out;
[0119] 7) Washing: Add ethanol and deionized water for ultrasonic dispersion, then centrifuge, repeat twice. Disperse the washed sample into a small amount of anhydrous ethanol for storage to obtain self-assembled one-dimensional platinum-cobalt alloy nanowires (PtFe NWs).
[0120] Example 7: A porous carbon-supported one-dimensional platinum cobalt nanowire (PtCo / C NWs), the preparation method of which comprises the following steps:
[0121] 1) Weigh 41.51 mg (0.1 mmol) of potassium chloroplatinite (K2PtCl4), 25.72 mg (0.1 mmol) of cobalt acetylacetonate (Co(acac)2) precursor and 100 mg of V_XC72 porous carbon black, grind them thoroughly in an agate mortar, mix them evenly, and obtain a precursor powder;
[0122] 2) The precursor powder is spread flat on a quartz boat, then placed in a quartz tube and placed in a tube furnace;
[0123] 3) Pass argon gas into the quartz tube for 20 minutes to exhaust the air in the quartz tube to prevent the metal from being oxidized during the heating process;
[0124] 4) Switch the gas to pure hydrogen at a flow rate of 200 ml / min; at the same time, raise the temperature of the tube furnace from room temperature to 180°C at a heating rate of 5°C / min and keep it at this temperature for 180 min;
[0125] 5) Switch the gas to a hydrogen / argon (v / v=5 / 95) mixed gas at a flow rate of 200 ml / min. At the same time, increase the temperature of the tube furnace from 180°C to 300°C at a heating rate of 5°C / min, keep it for 6 hours, and then cool it down naturally to room temperature;
[0126] 6) After the reaction is completed, the gas is switched to argon, the residual hydrogen in the quartz tube is evacuated, and the reduced solid powder product is taken out;
[0127] 7) Washing: Add ethanol and deionized water for ultrasonic dispersion, then centrifuge, repeat twice. Disperse the washed sample into a small amount of anhydrous ethanol for storage to obtain porous carbon-supported one-dimensional platinum cobalt nanowires (PtCo / C NWs).
[0128] Embodiment 8:
[0129] A porous carbon-supported one-dimensional platinum iron nanowire (PtFe / C NWs), a preparation method thereof and an oxygen reduction application thereof comprise the following steps:
[0130] 1) Weigh 41.51 mg (0.1 mmol) of potassium chloroplatinite (K2PtCl4), 35.32 mg (0.1 mmol) of iron acetylacetonate (Fe(acac)3) precursor and 100 mg of porous carbon black, grind them thoroughly in an agate mortar, mix them evenly, and obtain a precursor powder;
[0131] 2) The precursor powder is spread flat on a quartz boat, then placed in a quartz tube and placed in a tube furnace;
[0132] 3) Pass argon gas into the quartz tube for 20 minutes to exhaust the air in the quartz tube to prevent the metal from being oxidized during the heating process;
[0133] 4) Switch the gas to pure hydrogen at a flow rate of 200 ml / min; at the same time, raise the temperature of the tube furnace from room temperature to 200°C at a heating rate of 5°C / min and keep it at this temperature for 180 min;
[0134] 5) Switch the gas to a hydrogen / argon (v / v=5 / 95) mixed gas at a flow rate of 200 ml / min. At the same time, increase the temperature of the tube furnace from 200°C to 250°C at a heating rate of 5°C / min, keep the temperature for 5 hours, and then cool it down to room temperature naturally;
[0135] 6) After the reaction is completed, the gas is switched to argon, the residual hydrogen in the quartz tube is evacuated, and the reduced solid powder product is taken out;
[0136] 7) Washing: Add ethanol and deionized water for ultrasonic dispersion, then centrifuge, repeat twice. Disperse the washed sample into a small amount of anhydrous ethanol for storage to obtain self-assembled one-dimensional platinum-nickel alloy nanowires (Pt3Ni NWs).
[0137] Figure 1 The present invention is a process flow chart of the self-assembly preparation method of the platinum-based nanowire electrocatalytic material, which involves a two-part reduction method, has a simple process, and is easy to operate and industrially scale up. Figure 2 To characterize the morphology and structure of platinum-based alloy nanowires. Figure 2-1 TEM structural characterization of the one-dimensional platinum-nickel alloy nanowires prepared in Example 1. Figure 2-2 TEM structural characterization of the one-dimensional platinum-copper alloy nanowires prepared in Example 2. Figure 2-3 TEM structural characterization of the one-dimensional platinum-cobalt alloy nanowires prepared in Example 3. Figure 2-4 TEM structural characterization of the one-dimensional platinum-copper alloy nanowires prepared in Example 7; it shows that the preparation method involved in the present invention is suitable for the synthesis of various one-dimensional platinum-based binary nanowires.
[0138] Figure 3 TEM and particle size distribution diagrams of one-dimensional PtCo alloy nanowires of different proportions prepared in Examples 3-5. The diameters of the PtCo alloy nanowires of different proportions are 3.47nm, 5.14nm and 4.15nm, respectively. This shows that the preparation method of the present invention is applicable to the synthesis of platinum-based alloy nanowires of different proportions.
[0139] Figure 4 The XRD of one-dimensional PtCo alloy nanowires with different ratios prepared in Examples 3-5 and the proportion of Co in the nanowires prepared with different precursor ratios. XRD shows that the prepared nanowires are all single-phase alloys, and their Co ratios can be obtained from EDS, which are 44%, 15%, and 8%, respectively. The EDS results show that when the precursor molar ratio is Pt:Co=1:1, the molar ratio of the obtained nanowires is 1.3:1, which is close to 1:1, and the alloying effect of the nanowires is the best. When the precursor molar ratio Pt:Co=2:1 or 3:1, the Pt content in the nanowires is very high, and the Co atomic content is very low. The nanowires are PtCo alloys mainly composed of metal Pt.
[0140] Figure 5 Figures 5-1 and 5-2 correspond to the porous carbon-supported one-dimensional platinum-cobalt nanowires prepared in Example 7 and the porous carbon-supported one-dimensional platinum-iron nanowires prepared in Example 8, respectively, indicating that the preparation method of the present invention is not only applicable to self-assembled nanowires, but is also applicable in the presence of a carrier.
[0141] Figure 6 The electrocatalytic oxygen reduction performance of platinum-cobalt nanowires of different proportions prepared in Examples 3-5. The mass activity of Pt1Co1 nanowires is 8.6 times that of commercial platinum-carbon. The detailed data showing excellent oxygen reduction performance are shown in Table 1.
[0142] Table 1 Comparison of mass activity and specific activity of oxygen reduction electrocatalysis of platinum-cobalt alloy nanowire catalysts with different ratios
[0143]
[0144]
[0145] Figure 7 The electrocatalytic oxygen reduction stability results of the Pt3Ni1 nanowires prepared in Example 1. After 30,000 cycles of accelerated testing, the specific activity only lost 25%, and the mass activity only lost 30%, showing excellent oxygen reduction activity and stability. The detailed data are shown in Table 2.
[0146] Table 2 Comparison of mass activity and specific activity of Pt3Ni nanowire catalyst before and after 30,000 cycles of accelerated stability test for oxygen reduction
[0147]
[0148] Figure 8 The oxygen reduction catalytic performance of the PtCo nanowires prepared in Example 3 is compared with that of the PtCo nanowires prepared by reduction only at 200°C and only at 300°C. The mass activity of the PtCo alloy nanowire catalyst prepared by the two-step reduction method involved in the present invention is 5.29 and 3.64 times that of the PtCo alloy nanowires reduced only at 200°C and only at 300°C. This shows that the nanowires prepared by the two-step reduction method of the present invention have excellent oxygen reduction activity. Detailed data are shown in Table 3.
[0149] Table 3 Comparison of mass activity and specific activity of Pt1Co1 by two-step method and one-step method
[0150]
[0151] Fig. 9 The test results of the PtCo nanowires prepared in Example 3 and the commercial Pt / C catalyst in a fuel cell are shown in Table 4. The fuel cell test results show that the mass activity of the PtCo nanowires is 2.35 times that of the commercial Pt / C. More noteworthy is that after 30,000 cycles of accelerated life test, the mass activity of the platinum cobalt nanowire catalyst prepared by the present invention still retains 63.8%, and the maximum power density still retains 80.88%. However, the mass activity of the commercial Pt / C is only 30.0% of the original, and the power density is only 39.66% of the original. This shows that the platinum cobalt nanowires prepared by the present invention maintain excellent activity and stability in the fuel cell test. The detailed data are shown in Table 4.
[0152] Table 4 Comparison of fuel cell mass activity and power density between Pt1Co1 and commercial Pt / C
[0153]
[0154] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A self-assembly preparation method of platinum-based nanowire electrocatalytic material, characterized in that: include: The platinum precursor salt and the transition metal precursor salt are mixed, heated in a reducing gas for reduction, and then heated in a diluted reducing gas for self-assembly to obtain a platinum-based nanowire electrocatalytic material; Wherein, in the heating reduction, the reduction temperature is 100-200°C; in the heating self-assembly, the heating temperature is 250-300°C.
2. The self-assembly preparation method of platinum-based nanowire electrocatalytic material according to claim 1, characterized in that: The reducing gas is hydrogen; the diluted reducing gas is a mixture of hydrogen and inert gas.
3. The self-assembly preparation method of platinum-based nanowire electrocatalytic material according to claim 2, characterized in that: The content of the hydrogen is 5-10 vol%.
4. The self-assembly preparation method of platinum-based nanowire electrocatalytic material according to claim 1, characterized in that: In the transition metal precursor salt, the transition metal is selected from at least one of iron, nickel, copper or cobalt.
5. The self-assembly preparation method of platinum-based nanowire electrocatalytic material according to claim 1, characterized in that: In the platinum precursor salt and the transition metal precursor salt, the molar ratio of platinum to transition metal is (1-3):
1.
6. The self-assembly preparation method of platinum-based nanowire electrocatalytic material according to claim 1, characterized in that: The platinum precursor salt is chloroplatinite, and the transition metal precursor salt is selected from acetylacetonate.
7. The self-assembly preparation method of platinum-based nanowire electrocatalytic material according to claim 1, characterized in that: The platinum precursor salt and the transition metal precursor salt are mixed together, and the mixture is also mixed with a carrier.
8. The self-assembly preparation method of platinum-based nanowire electrocatalytic material according to claim 7, characterized in that: The carrier is selected from porous carbon powder or titanium dioxide nanoparticles, and the amount used is 80-120 mg / 0.1 mmol Pt.
9. A platinum-based nanowire electrocatalytic material, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. A use of the platinum-based nanowire electrocatalytic material as claimed in claim 9, characterized in that: The platinum-based nanowire electrocatalytic material is used as an electrode material for preparing a fuel cell.
Citation Information
Patent Citations
Preparation method for platinum nanowire net
CN105081341A
Preparation method of carbon-supported nano platinum alloy catalyst
CN104600326A
Fuel cell catalyst, preparation method and composite nano-carbon material
CN105119003A
Method for preparing one-dimensional platinum-based nano material based on assistance of reducing gas
CN110479250A
Preparation method and application of ordered low-platinum alloy catalyst
CN113113621A
